2004
DOI: 10.1155/s1110724304406123
|View full text |Cite
|
Sign up to set email alerts
|

The Change of Total Anthocyanins in Blueberries and Their Antioxidant Effect After Drying and Freezing

Abstract: This study examined the effects of freezing, storage, and cabinet drying on the anthocyanin content and antioxidant activity of blueberries (Vaccinium corymbosum L). Fresh samples were stored for two weeks at 5°C while frozen samples were kept for up to three months at −20°C. There were two drying treatments, one including osmotic pretreatment followed by cabinet drying and the other involving only cabinet drying. Total anthocyanins found in fresh blueberries were 7.2 ± 0.5 mg/g dry matter, expressed as cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
99
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(118 citation statements)
references
References 19 publications
11
99
3
3
Order By: Relevance
“…Anthocyanins leakage might happen due to dewaxing, which was caused by soaking during the pretreatment. This observation is comparable to the study by (Lohachoompol et al, 2004) who found that dewaxing weakened the berry cuticle and allowed the skin to rupture. This permitted some leakage from the exposed edges or undersurface of the torn skin to the pretreated solution that caused anthocyanins loss before the drying process.…”
Section: Anthocyaninssupporting
confidence: 89%
“…Anthocyanins leakage might happen due to dewaxing, which was caused by soaking during the pretreatment. This observation is comparable to the study by (Lohachoompol et al, 2004) who found that dewaxing weakened the berry cuticle and allowed the skin to rupture. This permitted some leakage from the exposed edges or undersurface of the torn skin to the pretreated solution that caused anthocyanins loss before the drying process.…”
Section: Anthocyaninssupporting
confidence: 89%
“…juice extraction and subsequently sold as a dried berry product. Despite the varied functions and health benefits of ANCs, they are very labile and undergo significant breakage and structural changes during storage and processing (Ochoa et al, 1999;Lohachoompol et al, 2004;Sadilova et al, 2006). Due to their highly reactive nature, ANCs readily degrade to colorless or brown compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In related work we have attempted to quantify the total phenolics and anthocyanins in V. corymbosum simple hydroethanolic extract and found that the total concentration of phenolic compounds, expressed as catequin equivalents) 5.66 ± 0.01 mg g -1 , while the anthocyanin content was 0.099 ± 0.05 mg g -1 for cyanidin, 0.063 ± 0.06 mg g -1 for delphinidin and 0.131 ± 0.06 mg g -1 for malvidin (Torri et al, 2007, in press). Despite the proven antioxidant effect of these anthocyanins (Lohachoompol et al, 2004) and the fact that several phenolic compounds have also shown antimutagenic properties (Matkowski and Wolniak, 2005;Ragunathan and Panneerselvam, 2007) the mutagenic potential of some phenolic compounds is well known (Huberman et al, 1976;Snyder and Hedli, 1996). Although further investigations will be necessary, is possible that some phenolic compounds present in V. corymbosum extract could be responsible for the clastogenic or aneugenic effect observed by us with the MN assay.…”
Section: Resultsmentioning
confidence: 89%
“…In recent decades interest in the anthocyanin content of some Vaccinium species has revived due to the pharmacological properties of anthocyanins, which includes antioxidant activity (Wang et al, 1997;Mazza et al, 2002;Lohachoompol et al, 2004), anti-inflammatory effects (Youdim et al, 2002), cardiovascular protection, antidiabetic properties, improvements to vision and inhibition of carcinogenesis (Cabrita and Andersen, 1999;Camire, 2000;Katsube et al, 2003). The fruits of the economically important northern highbush blueberry (Vaccinium corymbosum L.) are consumed in many countries throughout the world because they contain large amounts of antioxidants thought to be beneficial to health (Prior et al, 1998;Ehlenfeldt and Prior, 2001).…”
Section: Introductionmentioning
confidence: 99%